Efektivitas pendekatan konseling rational emotif behavioral dengan teknik reframing untuk meningkatkan kecerdasan emosional siswa sekolah menengah pertama - Yani, Wayan Winda; Suarni, Ni Ketut; Dharsana, I Ketut (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aims to determine the effectiveness of the rational emotive-behavioral counseling service approach with reframing techniques to improve the emotional intelligence of SMP Negeri 2 Singaraja students. The method used in this study is experimental. Sampling using random sampling technique. Collecting data using emotional intelligence questionnaire. The data analysis technique used parametric statistical analysis, namely by using the Paired-Sample T-Test with the help of the SPSS for Windows version 16.00 program. This research method aims to determine the effect of rational emotive behavioral counseling with reframing techniques in increasing students' emotional intelligence. The research design used was the Non-Equivalent Pre-test Post-test Control Group Design. This study focuses on the effectiveness of the rational emotive behavioral counseling approach with reframing techniques to improve students' emotional intelligence with the data collection technique used, namely a questionnaire.